PENGARUH ROH MENYALA-NYALA DALAM MELAYANI TUHAN MENURUT ROMA 12:11 TERHADAP SEMANGAT PELAYANAN MAHASISWA SEKOLAH TINGGI TEOLOGI DUTA PANISA JEMBER - Agus Kristiani Mendrofa (Alucio Dei, 2021)
The development of the era towards the millennial era has dragged people tohave an all-istan lifestyle and attitudes of individualism, pragmatism, and indifference to become stronger in the midst of life together. This attitude has crawled and influenced the lifestyle of servants of God and church activists so that it has an impact on what is the main task of servants of God as social beings and servants of God, namely to care for and serve one another. To maintain the spirit of service to others, it is necessary to have a burning spirit in the life of the servant of God. Therefore, this research is an analysis of how much influence a burning spirit according to Romans 12:11 has on the spirit of service. This study uses quantitative methods using descriptive experimental design in order to determine the effect of a burning spirit on the spirit of service. Based on the data analysis, the results of the calculation of the data with the help of SPSS 16.0 indicate that the burning spirit variable (X) has a significance value of 0.048 <0.05, it can be concluded that the burning spirit variable (X) has a significant effect on the variable. spirit of service (Y).